Impact of Quality Management Practices on Production Quality Performance: Examining the Role of Process Improvement and Lean Six Sigma - Khaled A. Al Falah; Veera Pandiyan Kaliani Sundram (Decision Making: Applications in Management and Engineering, 2025)
The study aimed to investigate the impact of quality management practices on production quality performance with a mediating effect of process improvement. We have also evaluated the Lean Six Sigma moderating effects. SPSS was used for both demographic and inferential analysis to empirically examine the hypothesis. Using a convenient sampling technique, data were collected from 275 employees of SMEs through structured questionnaires. Regression results show that quality management practices positively and significantly impact production quality performance and process improvement. On the other hand, process improvement also positively and significantly influences production quality performance. The indirect mediating effect of process improvement also mediates between quality management practices and production quality performance. In addition, moderation analysis shows that Lean Six Sigma positively strengthens the relationship between process improvement and production quality performance. These findings indicate that the incorporation of both process improvement and Lean Six Sigma significantly enhances the effectiveness of quality management practices in improving production quality performance. Furthermore, the study provides practical insights to SMEs manufacturing companies to optimize their production quality performance by focusing on process improvement and the utilization of Six Sigma roles.